Analysis of fatigue cracking of warm mix asphalt. Influence of the manufacturing technology. (May 2018) - Sol-Sánchez, M.; Fiume, A.; Moreno-Navarro, F.; Rubio-Gámez, M.C.
Highlights: Testing temperature is a key factor in analyzing the resistance to fatigue cracking of WMA. WMA could slow down the initiation of micro-damage at low temperatures in comparison with HMA. Similar resistance to fatigue cracking of WMA manufactured by different techniques to reduce the production temperature. Abstract: In recent decades, warm mix asphalts have been proven to provide a series of benefits in the field of asphalt mixture production. However, to exploit these advantages it is essential that these materials present a mechanical performance and durability that is at least equivalent to traditional hot mix asphalts. The short-term mechanical behavior of warm mix asphalt has been widely studied and compared to that offered by hot mix asphalts, however few analysis have been made in the long-term. Among the various failure modes, fatigue cracking is regarded as one of the main concerns that can arise during the long-term service life of asphalt pavements. Based on these considerations, the present paper conducts a comparative analysis of the fatigue cracking life of hot and warm mix asphalts produced through the three main technologies currently used to reduce the manufacturing temperature (chemical additives, organic additives, and the foaming process). The results reveal that warm mix asphalts present similar resistance to micro and macro-cracking development to that measured for hot mix asphalts under the different testing conditions, whilst there are no significant differences between the various types of technologies evaluated.